Defect-rich antibacterial material preparation method and application

CN122894997APending Publication Date: 2026-10-13GUANGDONG TECHNION ISRAEL INST OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610856446.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-15
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

铜基氧化物(Cu2O、CuO)常与ZnO复合,但Cu2O易光腐蚀,CuO还原能力弱

Benefits of technology

本发明通过尿素辅助煅烧,生成富缺陷的混合价态复合广谱抗菌材料Cu2O/CuO-ZnO。所得材料在可见光下对多种典型致病菌均表现出卓越的杀灭效果,在10~15分钟内即可实现99.99%以上的灭活率,在环境净化及生物医用领域具有广阔的应用前景,且制备工艺简单成本低,适合大规模工业化生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present application relates to a kind of defect-rich antibacterial material preparation method and application, belong to antibacterial material technical field.The antibacterial material preparation method of the present application includes the following steps: the copper source of specific ratio, zinc source, urea are mixed and pulverized, then calcination is carried out at specific temperature, and defect-rich Cu2 O / CuO-ZnO antibacterial material is obtained.The preparation method of the present application can prepare the broad-spectrum antibacterial material with excellent visible light response and high active oxygen yield.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of antibacterial materials technology, and in particular to a method for preparing and applying a defective antibacterial material. Background Technology

[0002] With rising public health standards, there is an urgent need for low-dose, long-term, broad-spectrum antibacterial materials. Traditional chlorine-based disinfectants pose a risk of producing carcinogenic byproducts, and their irritant and corrosive properties limit their application.

[0003] Photocatalytic antibacterial technology has gained attention due to its green and broad-spectrum nature; however, wide-bandgap semiconductors such as ZnO only respond to ultraviolet light, exhibit high recombination rates of photogenerated carriers, and lack sustained antibacterial activity in the dark. Constructing heterojunctions is a primary modification strategy. Copper-based oxides (Cu2O, CuO) are often combined with ZnO, but Cu2O is easily photocorroded, and CuO has weak reduction capabilities. Existing copper-zinc composite particles suffer from loose interfaces, easy aggregation, surface inertness, and a lack of oxygen vacancies, resulting in low charge separation efficiency and reactive oxygen yield. Noble metal materials are costly and pose environmental release risks; ion dissolution and coating methods do not combine photocatalysis with defect engineering, leading to poor inactivation of drug-resistant bacteria. Furthermore, preparation often requires organic solvents or multiple calcination steps, making the process cumbersome and difficult to scale up.

[0004] Therefore, there is an urgent need to develop a broad-spectrum antibacterial material with excellent visible light response and high reactive oxygen yield. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a method for preparing and applying a defective antibacterial material.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a method for preparing a defect-rich antibacterial material, comprising the following steps: mixing 0.2-0.4 parts by weight of a copper source, 0.6-1.4 parts by weight of a zinc source and 1 part by weight of a urea, and then sequentially pulverizing and calcining the mixture to obtain the defect-rich antibacterial material; wherein the calcination temperature is 300-450°C and the time is 3-8 h; the copper source comprises an organic copper salt, and / or the zinc source comprises an organic zinc salt.

[0007] This invention utilizes a specific ratio of copper and zinc sources, combined with a specific proportion of urea. After mixing and pulverizing, the three powders are thoroughly mixed and reach microscopic contact under mechanical force. Then, calcination is performed at a specific temperature to generate a defect-rich heterojunction mixed-valence Cu2O / CuO-ZnO antibacterial material. This invention employs a urea-assisted solventless solid-phase calcination strategy. Under these specific low-temperature, slow thermal decomposition conditions, the decomposition of organic ligands is incomplete and accompanied by trace releases of reducing gases (such as CO and H2). This localized reducing atmosphere competes with oxygen in the air, inducing the stable coexistence of Cu²⁺ / Cu⁺ mixed valence states and simultaneously "etching" high-concentration oxygen vacancies onto the newly formed ZnO lattice surface. The gas generated by urea decomposition induces high-density structural defects and lattice distortion in situ. These defect sites interact with the mixed Cu²⁺... + / Cu 2+ The synergistic effect of redox centers not only effectively redshifts the light absorption wavelength and broadens the visible light response range, but also acts as a trapping center for photogenerated charge carriers, significantly suppressing electron-hole recombination. This enhances charge separation efficiency and the generation kinetics of reactive oxygen species (ROS), enabling rapid and continuous generation of ROS on the material surface. Increased oxidative stress levels at the bacteria-material interface lead to effective growth inhibition and irreversible cell damage, thereby achieving rapid inactivation of both sensitive and antibiotic-resistant bacterial strains.

[0008] Maintaining the ratio of copper and zinc sources within the range specified in this invention ensures effective interfacial interactions in the material, preventing copper oxide agglomeration and decreased structural stability. When the copper source ratio is too low, copper oxides cannot form sufficient interfacial coupling, leading to insufficient interfacial charge separation and a significant decrease in antibacterial performance. Conversely, when the copper source ratio is too high, excessive agglomeration of copper oxides disrupts the material's structural balance, further degrading antibacterial performance. Maintaining the urea and zinc source ratio within the range specified in this invention stably generates a defect-rich heterojunction structure. When the urea content is too low, insufficient gaseous substances are released from urea decomposition, resulting in incomplete defect formation. When the urea content is too high, excessive decomposition gas generation leads to severe lattice distortion and excessive material structure collapse, impairing charge transport capacity and antibacterial performance. This invention strictly controls the calcination parameters. Too low a calcination temperature results in insufficient precursor decomposition and incomplete phase formation; too high a calcination temperature leads to defect annihilation, grain coarsening, and Cu... + / Cu 2+ The problem of imbalance in proportion: when the calcination time is too short, it will lead to insufficient phase transformation; when the calcination time is too long, the defect density will be abnormally increased due to structural relaxation, which will degrade the structural performance and antibacterial effect of the material.

[0009] In a preferred embodiment of the method for preparing the defective antibacterial material according to the present invention, the copper source includes one or more of copper acetate, copper sulfate, and copper chloride.

[0010] In a preferred embodiment of the method for preparing the defective antibacterial material according to the present invention, the zinc source includes one or more of zinc acetate dihydrate, zinc sulfate, and zinc chloride.

[0011] In a preferred embodiment of the method for preparing the defect-rich antibacterial material described in this invention, the pulverization is performed using one or more of dry grinding, dry ball milling, and air jet milling. Dry pulverization avoids the introduction of impurities by the liquid phase, and its mechanical energy can directly act on the defects introduced by the crystal lattice, which is beneficial to the formation of oxygen vacancies during subsequent calcination.

[0012] In a preferred embodiment of the method for preparing the defect-rich antibacterial material according to the present invention, the pulverization time is 20-60 min. If the pulverization time is too short, the material will not be sufficiently refined and defects will not be introduced; if the time is too long, the material may become excessively amorphous or be contaminated by the grinding media, weakening the crystallinity and activity of the material.

[0013] In a preferred embodiment of the method for preparing the defective antibacterial material described in this invention, the heating rate during calcination is 1~5℃ / min. A heating rate that is too low will significantly prolong the process cycle and reduce efficiency; a rate that is too high will easily generate a large temperature gradient, causing abnormal grain growth, which is detrimental to the uniform construction of oxygen vacancies and heterojunction interfaces.

[0014] In a preferred embodiment of the method for preparing the defective antibacterial material described in this invention, the calcination atmosphere includes air. An air atmosphere eliminates the need for inert gas protection, is low-cost, and its moderate oxygen partial pressure promotes the synergistic generation of mixed valence states and oxygen vacancies in copper-based oxides.

[0015] In a preferred embodiment of the method for preparing the defective antibacterial material described in this invention, the calcined material is spread evenly in a wide-bottomed container during the calcination process. This method increases the contact area between the material and air, ensuring uniform and thorough calcination, avoiding localized oxygen deficiency or overheating caused by accumulation, and ensuring a uniform distribution of defective structures.

[0016] Secondly, this invention provides a defect-rich antibacterial material prepared by the aforementioned method for preparing defect-rich antibacterial materials. This material constructs a Cu₂O / CuO-ZnO heterojunction rich in oxygen vacancies and Cu⁺ / Cu²⁺ mixed valence states, significantly enhancing visible light response and reactive oxygen species generation capacity, and exhibiting a rapid inactivation effect on drug-resistant strains.

[0017] Thirdly, this invention provides an application of a defect-rich antibacterial material for photocatalytic sterilization. This material can efficiently generate active species such as superoxide radicals under visible light irradiation, achieving a broad-spectrum and highly efficient sterilization effect.

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention utilizes urea-assisted calcination to generate a defect-rich, mixed-valence composite broad-spectrum antibacterial material, Cu2O / CuO-ZnO. The resulting material exhibits excellent bactericidal effects against a variety of typical pathogens under visible light, achieving an inactivation rate of over 99.99% within 10-15 minutes. It shows broad application prospects in environmental purification and biomedical fields, and its preparation process is simple and low-cost, making it suitable for large-scale industrial production. Attached Figure Description

[0019] Figure 1 The XRD patterns of the samples prepared in Example 1, Comparative Examples 5, and 8-9 of this invention are shown below. Figure 2 The images show the structure and defect characterization of the samples prepared in Examples 1, 1-2, and 5 of this invention, where (a) is a Raman spectrum and (b) is an electron paramagnetic resonance spectrum. Figure 3 These are microscopic morphology images of the samples prepared in Examples 1, 1-2, and 5 of this invention. (a) is the SEM morphology image of Comparative Example 1, (b) is the SEM morphology image of Comparative Example 2, (c) is the SEM morphology image of Comparative Example 5, (d) is the SEM morphology image of Example 1; (ef) is the transmission electron microscope image of Example 1. Figure 4 Comparison of the ultraviolet-visible diffuse reflectance spectra of the samples prepared in Example 1, Comparative Examples 1-2, and 5 of this invention; Figure 5 The images show the scanning electron microscope (SEM) morphology comparisons of four different bacteria before and after treatment with the samples prepared in Example 1 of this invention. (a) Untreated Escherichia coli, (bc) Treated Escherichia coli, (d) Untreated Bacillus megaterium, (ef) Treated Bacillus megaterium, (g) Untreated Edwardsiella tarda GT45, (hi) Treated Edwardsiella tarda GT45, (j) Untreated Escherichia coli ET5, (kl) Treated Escherichia coli ET5. Detailed Implementation

[0020] To better illustrate the purpose, technical solution, and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0021] All strains were cultured on Luria-Bertani medium, and single colonies were grown on LB medium containing 1.5% agar. For the growth of drug-resistant strains, the medium for antibiotic-resistant Edwardsiella tarda was supplemented with ampicillin (100 μg / mL) and chloramphenicol (25 μg / mL), while the medium for Gram-negative Escherichia coli was supplemented with ampicillin (64 μg / mL) and streptomycin (32 μg / mL). Cells were inoculated into test tubes, sealed with a breathable membrane, and cultured from single colonies at 37°C and 900 rpm shaking.

[0022] Unless otherwise specified, all other materials and reagents used in the examples are commercially available.

[0023] Pretreatment for bacterial SEM characterization: After photocatalyst treatment, the bacteria were washed twice with phosphate-buffered saline (PBS) to thoroughly remove residual culture medium and loosely attached particles. Then, 2.5% glutaraldehyde solution was added as a fixative, and the mixture was incubated at 4°C for 4 hours. After fixation, excess glutaraldehyde was removed by washing with PBS, and the bacteria were dehydrated using a gradient dehydration method: 10%, 30%, 50%, 70%, 90% ethanol, and anhydrous ethanol were used for dehydration for 20 minutes each. After dehydration, the bacteria dispersed in anhydrous ethanol were dropped onto a clean silicon wafer. After gold-plating for conductivity, the samples were observed for morphology using a Zeiss Gemini 450 scanning electron microscope.

[0024] The specific steps for the photocatalytic bactericidal activity test are as follows: The photocatalyst powder is dispersed in sterile physiological saline to prepare a 200 μg / mL stock solution suspension, and then reacted with a solution of 2×10⁻⁶ μg / mL. 7 Equal volumes of bacterial suspension with CFU / mL were mixed, resulting in a final photocatalyst concentration of 100 μg / mL and a bacterial concentration of 1×10⁻⁶. 7 CFU / mL; After stirring in the dark for 30 minutes to reach adsorption equilibrium, the mixed solution was irradiated with a 300 W xenon lamp equipped with a 400 nm cutoff filter to simulate visible light for 10-30 minutes to evaluate the effect of irradiation time on bacterial inactivation; Samples were taken at time intervals of 5, 10, 15, 20 and 25 minutes, and an appropriate amount of diluted bacterial solution was evenly spread on LB agar plates and incubated at 37°C for 24 hours. The sterilization rate was calculated by counting the number of bacterial colonies, using the following formula: Sterilization rate = (1 - number of colonies in the sample group / number of colonies in the control group) × 100%, to evaluate its photocatalytic antibacterial activity.

[0025] All measurements were repeated three times and the average value was taken.

[0026] Example 1 An embodiment of the method for preparing defective antibacterial materials according to the present invention, wherein the preparation method of this embodiment is as follows: S1. Accurately weigh 5.0 g of zinc acetate dihydrate, 1.5 g of copper acetate, and 5.0 g of urea.

[0027] S2. Place the above three powders in an agate mortar and grind them dry for 45 minutes.

[0028] S3. Spread the ground homogeneous mixture evenly in a wide-bottomed alumina crucible and place it in a muffle furnace. Heat to 350℃ at a heating rate of 2.3℃ / min and calcine at this temperature for 6 hours.

[0029] S4. After the calcined sample has cooled naturally to room temperature in the furnace, it is removed and exhibits a uniform dark gray-black color. Grinding it in an agate mortar yields a powder that is a defect-rich Cu2O / CuO-ZnO antibacterial material.

[0030] Example 2 The only difference between this embodiment and Example 1 is that the mass of copper acetate weighed is 1.0 g, while the other preparation steps and parameters are the same as in Example 1.

[0031] Example 3 The only difference between this embodiment and Example 1 is that the mass of copper acetate weighed is 2.0 g, while the other preparation steps and parameters are the same as in Example 1.

[0032] Comparative Example 1 The only difference between this embodiment and Example 1 is that no copper source and urea are added. The other preparation steps and parameters are the same as in Example 1, and the synthesized product is nano-ZnO nanowires.

[0033] Comparative Example 2 The only difference between this embodiment and Example 1 is that no zinc source and urea are added. The other preparation steps and parameters are the same as in Example 1, and the synthesis product is Cu2O / CuO.

[0034] Comparative Example 3 The only difference between this embodiment and Example 1 is that the mass of copper acetate weighed is 0.5 g, while the other preparation steps and parameters are the same as in Example 1.

[0035] Comparative Example 4 The only difference between this embodiment and Example 1 is that the mass of copper acetate weighed is 0.25 g, while the other preparation steps and parameters are the same as in Example 1.

[0036] Comparative Example 5 The only difference between this embodiment and Example 1 is that urea is not added; the other preparation steps and parameters are the same as in Example 1.

[0037] Comparative Example 6 The only difference between this embodiment and Embodiment 2 is that urea is not added; the other preparation steps and parameters are the same as in Embodiment 2.

[0038] Comparative Example 7 The only difference between this embodiment and Example 3 is that urea is not added; the other preparation steps and parameters are the same as in Example 3.

[0039] Comparative Example 8 The only difference between this embodiment and Example 1 is that the amount of urea added is 2.5 g; the other preparation steps and parameters are the same as in Example 1.

[0040] Comparative Example 9 The only difference between this embodiment and Example 1 is that the amount of urea added is 10 g; the other preparation steps and parameters are the same as in Example 1.

[0041] Comparative Example 10 The only difference between this embodiment and Example 1 is that the calcination temperature is 275℃, while the other preparation steps and parameters are the same as in Example 1.

[0042] Comparative Example 11 The only difference between this embodiment and Example 1 is that the calcination temperature is 475℃, while the other preparation steps and parameters are the same as in Example 1.

[0043] from Figure 1 As can be seen, the amount of urea added in the preparation method affects the defects of the defect-rich antibacterial material. In Comparative Example 8, with low urea content, the sample diffraction peaks are sharp and not significantly different from the sample without urea, indicating insufficient defect formation. In Example 1, with optimized content, the XRD characteristic peaks are clearly identifiable but moderately broadened, indicating increased defect density and intact heterojunction structure. In Comparative Example 9, with excessive urea, the XRD characteristic peaks are significantly weakened or even indistinguishable, indicating severe lattice distortion and amorphization of the material. In Comparative Example 5, the diffraction peaks of this sample are significantly broadened and weakened, indicating reduced grain size and increased lattice disorder. This phenomenon is attributed to the thermal decomposition behavior of urea during calcination: the released gaseous products (NH3, CO2) effectively inhibit excessive grain growth and agglomeration, and induce lattice distortion and structural defect formation. Furthermore, no characteristic peaks of impurity phase or graphitic carbon nitride (g-C3N4) were detected in the spectrum, indicating that in this synthesis system, urea only acts as a structure regulator and defect inducer, rather than a carbon / nitrogen dopant source or carbon nitride precursor.

[0044] from Figure 2 It can be seen that, as Figure 2The Raman spectrum of α shows that pure-phase ZnO exhibits typical Raman-active vibrational modes of a wurtzite structure, including the low wavenumber E2(low) vibration at 95 cm⁻¹ and the high wavenumber E2(high) vibration near 437 cm⁻¹, which correspond to the Zn sublattice vibration and the oxygen lattice vibration, respectively. The presence of these characteristic vibrational modes confirms that ZnO has good crystallinity. For the Cu₂O / CuO sample, the characteristic Ag and Bg Raman peaks corresponding to copper oxides appeared, confirming the formation of Cu₂O / CuO in the system. After constructing the 30Cu₂O / CuO-ZnO composite material, the characteristic vibrational modes of ZnO and copper oxides appeared simultaneously in the Raman spectrum, indicating the successful construction of the heterojunction. In the defect-rich 30Cu₂O / CuO-ZnO (5 g urea) sample, the E1(LO) vibrational mode near 578 cm⁻¹ showed a significant enhancement. The longitudinal optical phonon mode has been widely confirmed to be closely related to oxygen vacancies, lattice disorder, and defect-related scattering in ZnO-based materials. The increased intensity of this peak indicates that a higher concentration of defect sites is introduced into the material during urea-assisted synthesis. Furthermore, slight peak broadening in multiple vibrational modes suggests that the introduction of defects causes lattice distortion in the material. Oxygen vacancies in the material are mainly formed during urea-assisted heat treatment: reducing gases such as NH3 produced by urea decomposition create a localized reducing atmosphere, which can remove some lattice oxygen from the metal oxide framework, thus forming oxygen vacancy defects. In addition, the interaction at the Cu2O / CuO-ZnO heterostructure interface induces lattice distortion and charge imbalance, which can further stabilize and promote the formation of oxygen vacancies in the composite structure. Figure 2 The EPR test results of b provide direct evidence for the existence of paramagnetic defect centers. Compared with ZnO, Cu2O / CuO, and conventional Cu2O / CuO-ZnO composites, the defect-rich Cu2O / CuO-ZnO (5 g urea) sample exhibits a very strong EPR characteristic signal, which is a characteristic response of unpaired electrons associated with oxygen vacancies and defect sites. The significant increase in signal intensity directly confirms that the defect concentration in the urea-modified material is greatly increased, which is highly consistent with the Raman spectroscopy analysis results and clearly highlights the structural difference between the material of this invention and the defect-free materials of the prior art.

[0045] Depend on Figure 3 As can be seen, in Comparative Example 1, pure ZnO exhibits a typical rod-like structure with uniform size and tight packing. Figure 3 a) reflects the preferred growth habit during the thermal decomposition of zinc acetate. Comparative Example 2 shows the opposite: the Cu2O / CuO sample exhibits irregular micro / nano clusters with rough surfaces and dense packing, which is due to disordered crystal growth caused by the lack of structure-directing agents. Figure 3 b). In Comparative Example 5, for the conventional 30Cu2O / CuO-ZnO composite material ( Figure 3c) The morphology underwent significant reconstruction, presenting as a heterogeneous assembly of small particles, indicating that the introduction of copper species inhibited the one-dimensional growth of ZnO to some extent. In Example 1, the defect-rich Cu2O / CuO-ZnO sample after urea-modified treatment exhibited the most unique structural features ( Figure 3 d): The particle size further decreased, and the aggregates exhibited a highly loose, porous, fragmented morphology with blurred grain boundaries. This structural evolution stems from the "gas expansion effect" generated by urea decomposition, which not only blocked mass transfer and fusion between grains but also promoted the formation of defect-rich mixed-valence nanoscale regions. Transmission electron microscopy analysis of the defect-rich composite material prepared in Example 1 ( Figure 3 (ef) confirmed that the material generated interconnected nanoscale particles with interplanar spacings of 0.25 nm, 0.24 nm, and 0.22 nm corresponding to the (002) crystal plane of ZnO, the (111) crystal plane of Cu2O, and the (111) crystal plane of CuO, respectively. The coexistence of the above lattice fringes and clear interface boundaries confirms the formation of a multiphase coupled structure and heterojunction in the material.

[0046] Figure 4 The UV-Vis diffuse reflectance spectroscopy results show that pure ZnO exhibits intrinsic absorption only in the UV region due to its wide bandgap characteristics. After introducing a narrow bandgap Cu2O / CuO composite material, the absorption edge undergoes a significant redshift, and the absorption intensity in the visible light region is significantly enhanced. Most importantly, the defect-rich Cu2O / CuO-ZnO sample prepared in Example 1 exhibits the widest absorption range and the strongest visible light trapping ability. The tailing phenomenon of its absorption band is attributed to the sub-bandgap energy levels introduced by numerous structural defects (such as oxygen vacancies), which greatly promotes the excitation and utilization of low-energy photons.

[0047] Example of effect 1 This example investigated the effect of copper precursor content during preparation on the antibacterial properties of the defect-rich Cu2O / CuO-ZnO photocatalyst of this invention. The tested bacteria was *Escherichia coli*. The experimental results regarding the antibacterial properties against *E. coli* are shown in Table 1.

[0048] Table 1 As can be seen from the table, the bactericidal effect is best when the ratio of copper source to zinc source is (0.2~0.4):1 during the preparation process. When the amount of copper source added is too large or too small, the bactericidal effect is low. This shows that the antibacterial performance of the material of the present invention is not a simple function of copper content, but the result of the synergistic optimization of heterojunction formation, defect density and crystallinity.

[0049] Example 2 This study investigated the antibacterial activity of the antimicrobial materials of Examples 1, 1-2, and 5 of the present invention against different bacteria. The test subjects included four representative bacterial strains: *Escherichia coli* (Gram-negative), *Bacillus megaterium* (Gram-positive), antibiotic-resistant Edwardsiella tarda (GT45), and antibiotic-resistant *Escherichia coli* (ET5). The bactericidal effects on *Escherichia coli* are shown in Table 2-1; the bactericidal effects on *Bacillus megaterium* are shown in Table 2-2; the bactericidal effects on antibiotic-resistant Edwardsiella tarda are shown in Table 2-3; and the bactericidal effects on antibiotic-resistant *Escherichia coli* are shown in Table 2-4.

[0050] Table 2-1 Table 2-2 Table 2-3 Table 2-4 As can be seen from Tables 2-1 to 2-4, the antibacterial material of the present invention has a broad-spectrum bactericidal effect, and exhibits rapid and thorough bacterial inactivation effect on all tested strains.

[0051] The morphological changes of bacterial cells after photocatalytic treatment with defect-rich mixed-valence Cu2O / CuO-ZnO prepared in Example 1, which showed the highest antibacterial efficiency, were further analyzed using SEM. Figure 5 It can be seen that the control group of Escherichia coli ( Figure 5 a) Bacillus megaterium ( Figure 5 d) Antibiotic-resistant Edwardsiella tarda (GT45) Figure 5 g) and antibiotic-resistant Escherichia coli (ET5) ( Figure 5 j) All strains exhibited intact cell morphology, with smooth surfaces, clear rod-like shapes, and complete cell membrane structures, indicating good cell integrity before treatment. In contrast, after photocatalytic treatment with a defect-rich mixed-valence Cu2O / CuO-ZnO (5 g urea) composite material, all strains showed severe morphological damage. Figure 5 As shown in bc, the surface of E. coli cells becomes rough and wrinkled, and the cell membrane is clearly ruptured, collapsed, and broken; Bacillus megaterium (… Figure 5 After treatment, *Edwards ef* showed severe deformation, cell wall damage, and leakage of intracellular material, indicating a loss of cell membrane integrity; similarly, *Edwards tachycardiae* GT45 (… Figure 5 (hi) Photocatalytic treatment resulted in significant structural collapse and cell lysis; the treated Escherichia coli (ET5) strain ( Figure 5The *kl* (Cu₂O / CuO-ZnO) also exhibited extensive membrane damage and cell debris aggregation. These morphological changes are typical of reactive oxygen species (ROS)-induced oxidative damage generated by defect-rich mixed-valence Cu₂O / CuO-ZnO under visible light irradiation. The abundant surface defects and mixed-valence Cu₂O... + / Cu 2+ The center promotes the rapid generation of ROS, which attack bacterial cell membranes, denature proteins, and ultimately lead to irreversible cell death.

[0052] Example 3 To investigate the effects of urea addition amount, urea dosage, and calcination temperature on the antibacterial properties of the defect-rich Cu2O / CuO-ZnO photocatalyst of this invention, we conducted Examples 1-3 and Comparative Examples 6-11 to examine its antibacterial effect against antibiotic-resistant Edwardsiella tarda. The antibacterial and sterilization results are summarized in Table 3.

[0053] Table 3 As shown in Table 3, adding urea is beneficial to generating defect-rich Cu2O / CuO-ZnO, thereby improving the sterilization efficiency. When the amount of urea added is too low or too high, the sterilization efficiency is low. When preparing Cu2O / CuO-ZnO, the sterilization efficiency of the prepared Cu2O / CuO-ZnO is low when the calcination temperature is too high or too low.

[0054] Example of effect 4 This example investigated the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the antimicrobial material of the present invention. The MIC and MBC were determined using the standard microdilution method.

[0055] The MIC determination procedure is as follows: The photocatalyst stock suspension was washed twice with ethanol, followed by serial dilutions with LB medium in a sterile 96-well microtiter plate. The bacterial culture cultured overnight was adjusted to a concentration of 1×10⁻⁶ with fresh LB medium. 7 CFU / mL. Subsequently, 10 μL of bacterial inoculum was added to each well containing 100 μL of photocatalyst suspension, and the mixture was incubated at 37°C for 24 hours. Wells without added photocatalyst served as positive controls, and wells without added bacterial inoculum served as negative controls. MIC is the lowest photocatalyst concentration that inhibits the growth of visible bacteria.

[0056] The MBC assay procedure is as follows: Take 30 μL of clear suspension from each MIC well with no visible growth, spread it onto an LB agar plate, and incubate at 37°C for 24 hours. The lowest concentration with fewer than 5 colonies is recorded as the MBC value.

[0057] Among them, MIC is shown in Table 4-1; MBC is shown in Table 4-2.

[0058] Table 4-1 Table 4-2 As shown in Tables 4-1 and 4-2, all materials exhibited high MIC and MBC values ​​under dark conditions, indicating limited inherent antibacterial and bactericidal activities without photoactivation. Pure ZnO showed the weakest performance, reflecting its limited redox activity and poor visible light response. Compared to ZnO, the Cu2O / CuO sample showed slightly improved antibacterial and bactericidal activities, attributed to the inherent redox properties of mixed-valence copper oxides. However, the MIC and MBC values ​​of this sample remained relatively high, especially against drug-resistant strains, confirming that dark activity alone was insufficient for effective bacterial inhibition and killing. However, under visible light irradiation, the MIC and MBC values ​​of all photocatalysts decreased significantly, indicating that the photocatalytic process plays a crucial role in bacterial inactivation. Compared to ZnO and Cu2O / CuO, the defect-rich mixed-valence 30% Cu2O / CuO-ZnO (5 g urea) composite material showed significantly enhanced antibacterial and bactericidal properties, indicating a clear synergistic effect between copper oxides and ZnO.

[0059] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A method for preparing a defect-rich antibacterial material, characterized in that, The method includes the following steps: by weight, 0.2-0.4 parts of copper source, 0.6-1.4 parts of zinc source, and 1 part of urea are mixed and then pulverized and calcined sequentially to obtain a defect-rich antibacterial material; wherein the calcination temperature is 300-450℃ and the time is 3-8 h; the copper source includes organic copper salt, and / or the zinc source includes organic zinc salt.

2. The method for preparing defect-rich antibacterial materials as described in claim 1, characterized in that, The copper source includes one or more of copper acetate, copper sulfate, and copper chloride.

3. The method for preparing defect-rich antibacterial materials as described in claim 1, characterized in that, The zinc source includes one or more of zinc acetate dihydrate, zinc sulfate, and zinc chloride.

4. The method for preparing defect-rich antibacterial materials as described in claim 1, characterized in that, The pulverization includes one or more of dry grinding, dry ball milling, and air jet milling.

5. The method for preparing defect-rich antibacterial materials as described in claim 1, characterized in that, The pulverization time is 20-60 minutes.

6. The method for preparing defect-rich antibacterial materials as described in claim 1, characterized in that, The heating rate during calcination is 1~5℃ / min.

7. The method for preparing defect-rich antibacterial materials as described in claim 1, characterized in that, The atmosphere during calcination includes air.

8. The method for preparing defect-rich antibacterial materials as described in claim 1, characterized in that, During the calcination process, the pulverized material is spread evenly in a wide-bottomed container for calcination.

9. A defective antibacterial material, characterized in that, The material is prepared by the method for preparing defective antibacterial materials as described in any one of claims 1 to 8.

10. The application of the defect-rich antibacterial material of claim 9 in photocatalytic sterilization.